Aphid gene expression following polerovirus acquisition is host species dependent - Pandey, Sudeep; Catto, Michael; Roberts, Phillip; Bag, Sudeep; Jacobson, Alana L.; Srinivasan, Rajagopalbabu (Frontiers in Plant Science, 2024)
Upon acquisition of persistent circulative viruses such as poleroviruses, the virus particles transcytose through membrane barriers of aphids at the midgut and salivary glands via hemolymph. Such intricate interactions can influence aphid behavior and fitness and induce associated gene expression in viruliferous aphids. Differential gene expression can be evaluated by Omics approaches such as transcriptomics. Previously conducted aphid transcriptome studies used only one host species as the source of virus inoculum. Viruses typically have alternate hosts. Hence, it is not clear how alternate hosts infected with the same virus isolate alter gene expression in viruliferous vectors. To address the question, this study conducted transcriptomic analysis of viruliferous aphids that acquired the virus from different host species. A polerovirus, cotton leafroll dwarf virus (CLRDV), induced gene expression in the cotton aphid, Aphis gossypii Glover, was assessed using four alternate hosts viz., cotton, hibiscus, okra, and prickly sida. Among a total of 2942 differentially expressed genes (DEGs), 750, 310, 1193, and 689 genes were identified in A. gossypii that acquired CLRDV from infected cotton, hibiscus, okra, and prickly sida, respectively, compared with non-viruliferous aphids that developed on non-infected hosts. A higher proportion of aphid genes were overexpressed than underexpressed following CLRDV acquisition from cotton, hibiscus, and prickly sida. In contrast, more aphid genes were underexpressed than overexpressed following CLRDV acquisition from okra plants. Only four common DEGs (heat shock protein, juvenile hormone acid O-methyltransferase, and two unannotated genes) were identified among viruliferous aphids from four alternate hosts. GO enrichment analysis and KEGG annotations indicated that the acquisition of CLRDV induced DEGs in aphids associated with virus infection, signal transduction, immune systems, and fitness. However, these induced changes were not consistent across four alternate hosts. These data indicate that alternate hosts could differentially influence gene expression in aphids and presumably aphid behavior and fitness despite being infected with the same virus isolate.